Szczelina Griffitha i Walcowa Inkluzja Kołowa w Antypłaskim Stanie Odkształcenia - Kaczyński, A. (Engineering Transactions, 1973)
An infinite elastic body containing a Griffith crack and a circular cylindrical inclusion of different elastic material, is subject to an antiplane state of strain under the action of uniformly distributed shearing forces. The main aim of the paper consists in the determination of the influence: of the inclusion on the state of stress around the crack, and on the stress intensity factor at the crack tip in particular. A method of consecutive approximations (the first and second approximations) is used.